Mathematics
         
语言:中文    Language:English
On line Solution of Monovariate Equation:
    Input any unary equation directly, and then click the "Next" button to obtain the solution of the equation.
    It supports equations that contain mathematical functions.
    Current location:Equations > Monovariate Equation > The history of univariate equation calculation > Answer

    Overview: 1 questions will be solved this time.Among them
           ☆1 equations

[ 1/1 Equation]
    Work: Find the solution of equation 1/(d+1)+1/(d+2)+1/(d+5) = 0 .
    Question type: Equation
    Solution:Original question:
     1 ÷ ( d + 1) + 1 ÷ ( d + 2) + 1 ÷ ( d + 5) = 0
     Multiply both sides of the equation by:( d + 1)
     1 + 1 ÷ ( d + 2) × ( d + 1) + 1 ÷ ( d + 5) × ( d + 1) = 0
    Remove a bracket on the left of the equation::
     1 + 1 ÷ ( d + 2) × d + 1 ÷ ( d + 2) × 1 + 1 ÷ ( d + 5) × ( d + 1) = 0
    The equation is reduced to :
     1 + 1 ÷ ( d + 2) × d + 1 ÷ ( d + 2) + 1 ÷ ( d + 5) × ( d + 1) = 0
     Multiply both sides of the equation by:( d + 2)
     1( d + 2) + 1 d + 1 + 1 ÷ ( d + 5) × ( d + 1)( d + 2) = 0
    Remove a bracket on the left of the equation:
     1 d + 1 × 2 + 1 d + 1 + 1 ÷ ( d + 5) × ( d + 1)( d + 2) = 0
    The equation is reduced to :
     1 d + 2 + 1 d + 1 + 1 ÷ ( d + 5) × ( d + 1)( d + 2) = 0
    The equation is reduced to :
     2 d + 3 + 1 ÷ ( d + 5) × ( d + 1)( d + 2) = 0
     Multiply both sides of the equation by:( d + 5)
     2 d ( d + 5) + 3( d + 5) + 1( d + 1)( d + 2) = 0
    Remove a bracket on the left of the equation:
     2 d d + 2 d × 5 + 3( d + 5) + 1( d + 1)( d + 2) = 0
    The equation is reduced to :
     2 d d + 10 d + 3( d + 5) + 1( d + 1)( d + 2) = 0
    Remove a bracket on the left of the equation:
     2 d d + 10 d + 3 d + 3 × 5 + 1( d + 1)( d + 2) = 0
    The equation is reduced to :
     2 d d + 10 d + 3 d + 15 + 1( d + 1)( d + 2) = 0
    The equation is reduced to :
     2 d d + 13 d + 15 + 1( d + 1)( d + 2) = 0
    Remove a bracket on the left of the equation:
     2 d d + 13 d + 15 + 1 d ( d + 2) + 1 × 1( d + 2) = 0
    The equation is reduced to :
     2 d d + 13 d + 15 + 1 d ( d + 2) + 1( d + 2) = 0
    Remove a bracket on the left of the equation:
     2 d d + 13 d + 15 + 1 d d + 1 d × 2 = 0
    The equation is reduced to :
     2 d d + 13 d + 15 + 1 d d + 2 d + 1 = 0
    The equation is reduced to :
     2 d d + 15 d + 15 + 1 d d + 1( d + 2) = 0
    Remove a bracket on the left of the equation:
     2 d d + 15 d + 15 + 1 d d + 1 d + 1 = 0
    The equation is reduced to :
     2 d d + 15 d + 15 + 1 d d + 1 d + 2 = 0
    The equation is reduced to :
     2 d d + 16 d + 17 + 1 d d = 0

    The solution of the equation:
        d1≈-3.868517 , keep 6 decimal places
        d2≈-1.464816 , keep 6 decimal places
    
    There are 2 solution(s).


解程的详细方法请参阅:《方程的解法》



Your problem has not been solved here? Please go to the Hot Problems section!





  New addition:Lenders ToolBox module(Specific location:Math OP > Lenders ToolBox ),welcome。